2023
DOI: 10.3399/bjgp.2022.0570
|View full text |Cite
|
Sign up to set email alerts
|

Adapting domestic abuse training to remote delivery during the COVID-19 pandemic: a qualitative study of views from general practice and support services

Abstract: Background: Identifying and responding to patients affected by domestic violence and abuse (DVA) is vital in primary care. There may have been a rise in the reporting of DVA cases during the COVID-19 pandemic and associated lockdown measures. Concurrently general practice adopted remote working which extended to training and education. IRIS (Identification and Referral to Improve Safety) is an example of an evidence-based UK healthcare training support and referral programme, focusing on DVA. IRIS transitioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The majority of advocates also reported positive support outcomes for their service users, although difficulties accessing onward support (creating a need to emotionally ‘hold’ service users while they waited for other support) were highlighted. This finding could be due to the precise and unusual set of circumstances brought about by the pandemic and accompanying national lockdowns rather than remote support per se; many other usual support services became (at least partially) unavailable during the first lockdown [ 36 – 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of advocates also reported positive support outcomes for their service users, although difficulties accessing onward support (creating a need to emotionally ‘hold’ service users while they waited for other support) were highlighted. This finding could be due to the precise and unusual set of circumstances brought about by the pandemic and accompanying national lockdowns rather than remote support per se; many other usual support services became (at least partially) unavailable during the first lockdown [ 36 – 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A report by the Health Foundation highlighted that many healthcare services had to adapt as a result of the pandemic and move towards a remote mode of working and that, in general, services that managed to adapt well relied on quickness and responsiveness as enablers of change [ 39 ]. A directly comparable qualitative study, aiming to understand the adaptations and impact of remote DVA training in IRIS-trained general practices by exploring perspectives of those delivering and receiving training [ 38 ] found benefits to widening the accessibility of training to greater numbers of busy healthcare professionals. This research reported a distinct trade-off between accessibility and levels of engagement – an anxiety shared by many of our participants.…”
Section: Discussionmentioning
confidence: 99%